The Effect of the Product, Price, Place and Promotion on the Customer Satisfaction According to the Islamic Perspective - Farid Khairi; Abdul Latif (Universitas Darussalam Gontor, 2024)
The marketing mix (Product, Price, Place, and Promotion) is essential in achieving buyer satisfaction, especially from the Islamic perspective. This quantitative research study aims to test the effect of the marketing mix on buyer satisfaction from an Islamic perspective, especially in the case of the La Tansa Sandal Factory. This study used multiple linear regression analysis methods and involved 200 respondents. La Tansa Sandal Factory is a business unit of Darussalam Gontor Islamic Boarding School, an Islamic educational institution that has achieved economic independence through a successful economic protection program. The results showed that the product variable (X1) had a significant positive effect on customer satisfaction (Y), while the price variable (X2) had a significant adverse impact on customer satisfaction (Y). The place variable (X3) also has a negative and insignificant effect on customer satisfaction (Y), while the promotion variable (X4) has a positive and significant impact on customer satisfaction (Y). These findings highlight the urgency of the marketing mix on buyer satisfaction, emphasizing the importance of product quality and promotional strategies in improving customer satisfaction from an Islamic perspective. La Tansa Sandals Manufacturers should focus on increasing their products' uniqueness, universality, relevance, and quality. They can research to understand the needs and preferences of their customers and develop products that meet those needs. They can also invest in product design and innovation to differentiate themselves. Keywords: Marketing Mix 4P, Customer Satisfaction, Islamic Marketing